ANALYZING COEFFICIENT OF RESTITUTION IN FREEFALL AND PENDULUM COLLISION METHODS - Adhitama, Rizky
The coefficient of restitution is the kinetic transition energy of an object just before and when it approves the impact. The coefficient of restitution is a characteristic of an object for successful observers, the motion of an object that is difficult to solve. Testing the restitution coefficient in this study discusses the pendulum free and collision method. The goal agreed in this study was to determine the value of the coefficient of restitution by two different methods. The free-fall method relates the hull time of the collision compilation object, while the pendulum collision method measures the angular velocity just before and then on the pendulum system fixing the collision with a smart application device and application to support changing objects in video format. The data presented consists of a graph of the sound produced by the compilation of objects striking the reflecting plane as well as the height of the bounce reflection for the free method, then graphs of angular velocity with time of the pendulum collision system produce data taken directly from the safe device video analysis which collides the reflection field restitution is then compared with conventional method data used as a reference and the value of the restitution coefficient is based on the reference restitution coefficient value.